Use of endoscopic distal attachment cap to enhance image stabilization in probe-based confocal laser endomicroscopy in colorectal lesions - Ussui, Vivian; Xu, Can; Crook, Julia E.; Diehl, Nancy N.; Hardee, Joy; Staggs, Estela G.; Shahid, Muhammad W.; Wallace, Michael B. (Endoscopy International Open, 2015)
Background and study aims: Colorectal cancer can be prevented through the use of colonoscopy with polypectomy. Most colon polyps are benign or low grade adenomas. However, currently all lesions need histopathologic analysis, which increases diagnostic costs and delays the final diagnosis. Confocal laser endomicroscopy (CLE) is a new technology that enables real-time endomicroscopy. However, there are challenges to maintaining a stable image with currently available systems. We conducted a small study to obtain a preliminary assessment of whether the use of an endoscopic distal attachment cap may enhance image quality of CLE in comparison with images obtained with free-hand acquisition.Patients and methods: Forty outpatients underwent colonoscopy for evaluation of colon polyps in a single academic medical center. Patients were assigned randomly to 1 of 2 study arms on the basis of whether an endoscopic distal attachment cap was used (n = 21, Cap Used) or not used (n = 19, No Cap) in the procedure. The quality of confocal images and probe stabilization was summarized.Results: A total of 81 polyps were identified. The proportion of polyps with images of high quality was 74 % (28/38) in the Cap Used group and 79 % (30/38) in the No Cap arm. Image stability was also similar with and without a cap. Diagnostic accuracy was estimated to be slightly higher in the Cap Used group for probe-based confocal laser endomicroscopy (pCLE; 78 % vs 70 %). This was also true for white-light and narrow-band imaging.Conclusions: This preliminary study did not yield any evidence to support that the use of an endoscopic distal attachment cap improves the quality of images obtained during CLE.